Слепняки рода Phytocoris Fiеb. (Heteroptera, Miridae) фауны Кавказа - Пучков, В.Г. (Вестник зоологии, 1978)
The new species of the genus Phytocoris: Ph. (Ribautomiris) parrotiae, Ph. (Eckerleinius) astragali, Ph. (Eriamiris) friganae, Ph. (E.) migrensis ssp. n. are described and key for the Caucasian species is given.